Autonomic Dysfunction Increases Cardiovascular Risk in the Presence of Sleep Apnea - Milagro, Javier; Deviaene, Margot; Gil, Eduardo; Lázaro, Jesús; Buyse, Bertien; Testelmans, Dries; Borzée, Pascal; Willems, Rik; Van Huffel, Sabine; Bailón, Raquel; Varon, Carolina (Frontiers in Physiology, 2019)
The high prevalence of sleep apnea syndrome (SAS) and its direct relationship with an augmented risk of cardiovascular disease (CVD) have raised SAS as a primary public health problem. For this reason, extensive research aiming to understand the interaction between both conditions has been conducted. The advances in non-invasive autonomic nervous system (ANS) monitoring through heart rate variability (HRV) analysis have revealed an increased sympathetic dominance in subjects suffering from SAS when compared with controls. Also HRV analysis of subjects with CVD suggests altered autonomic activity. In this work, we analyzed how altered autonomic control is reflected in subjects suffering from SAS and CVD (or at high risk of CVD) simultaneously, when compared with SAS patients. The analysis was performed over 199 subjects during night-time, and the effects of the physiological response that follows an apneic episode, sleep stages and respiration on HRV were taken into account. Results, as measured by HRV, suggest a decreased sympathetic dominance in those subjects suffering from both conditions, which was reflected in a significantly reduced sympathovagal balance (p < 0.05). In this way, ANS monitoring could contribute to patient phenotyping, as an altered response might have direct implications on cardiovascular health.